Bifunctional Cs−Au/Co3O4 (Basic and Redox)‐Catalyzed Oxidative Synthesis of Aromatic Azo Compounds from Anilines. Issue 36 (27th September 2021) - Oseghale, Charles O.; Fapojuwo, Dele Peter; Alimi, Oyekunle Azeez; Akinnawo, Christianah Aarinola; Mogudi, Batsile M.; Onisuru, Oluwatayo Racheal; Meijboom, Reinout
Abstract: An eco‐friendly alkali‐promoted (Cs−Au/Co3 O4 ) catalyst, with redox and basic properties for the oxidative dehydrogenative coupling of anilines to symmetrical and unsymmetrical aromatic azo compounds, was developed. We realized a base additive‐ and molecular O2 oxidant‐free process (using air), with reasonable reusability of the catalyst achieved under milder reaction conditions. Notably, the enhanced catalytic activity was also linked to the increased basic site concentration, low reduction temperatures, and the effect of lattice oxygen on the nanomaterials. The increased basic strength of the cation‐promoted catalyst improved the electron density of the active Au species, resulting in higher yields of the desired aromatic azo compounds. Abstract : An alkali‐promoted gold‐based (Cs−Au/Co3 O4 ) catalyst with redox and basic properties was designed to perform the oxidative coupling of anilines to symmetrical and unsymmetrical aromatic azo compounds. The process proceeded under milder reaction conditions without base additive and molecular O2 oxidant (using air). The catalyst performance was easily correlated to the effect of lattice oxygen, low reduction temperatures, and increased basic site concentrations, with reusability achieved up to six cycles.